Quantitative evaluation of p16INK4a promoter methylation using pyrosequencing in de novo diffuse large B-cell lymphoma - Zainuddin, Norafiza; Kanduri, Meena; Berglund, Mattias; Lindell, Monica; Amini, Rose-Marie; Roos, Göran; Sundström, Christer; Enblad , Gunilla; Rosenquist, Richard (Pergamon, 2011)
The p16INK4a tumor suppressor gene can be inactivated by a variety of events including promoter hypermethylation. In diffuse large B-cell lymphoma (DLBCL), p16INK4a methylation has been associated with advanced disease stage and higher IPI. The prognostic impact of p16INK4a methylation in DLBCL remains unclear; however, it has been suggested to correlate with inferior outcome. To further investigate the clinical impact of p16INK4a methylation in DLBCL, promoter methylation of this gene was assessed quantitatively by pyrosequencing. Forty-two of 113 (37%) DLBCL patients with methylation level above 5% were categorized as methylated and subsequently divided into low, intermediate and high methylation categories. Overall, no association was shown between the extent of p16INK4a methylation and patients’ clinical characteristics, except disease stage (P = 0.049). Moreover, we could not reveal any impact of p16INK4a methylation on lymphoma-specific survival. Although >25% of p16INK4a methylation correlated with a better progression-free survival (P = 0.048) in patients <65 years old, the significance of this finding, if any, needs to be further investigated. In conclusion, our finding questions the role of p16INK4a promoter methylation as a negative prognostic factor in DLBCL.